New empirical mass-loss recipe for UV radiation line-driven winds of hot stars across various metallicities - Pauli, Daniel; Oskinova, L. M.; Hamann, W.-R.; Sander, Andreas A. C.; Vink, J. S.; Bernini Peron, Matheus; Josiek, Joris; Lefever, Roel; Sana, H.; Ramachandran, Varsha (Astronomy and astrophysics, 2025)
Methods. We compile a sample of hot stars with reliable stellar and wind parameters in the Galaxy and the Magellanic Clouds. Our sample spans effective temperatures from T ≈ 12−100 kK and initial masses from Mini ≈ 15 M⊙-150 M⊙. The sample is used to determine the dependence of the mass-loss rate on the basic stellar parameters. - Results. We find that independent of evolutionary stage and temperature, the wind mass-loss rate is a function of the electronscattering Eddington parameter (Γe) and metallicity (Z), being in line with expectations of radiation-driven wind theory. Our derived scaling relation provides an adequate (∆ log(M˙ /( M⊙ yr−1)) = 0.43) and broadly applicable mass-loss recipe for hot stars. - Conclusions. The newly derived mass-loss recipe covers nearly the entire parameter space of hot stars with UV radiation-driven winds and eliminates the need for interpolation between mass-loss formulae at different evolutionary stages when applied in stellar evolution models. Examples of stellar evolution calculations using our new recipe reveal that the predictions on the ionizing fluxes and final fates of massive stars, especially at low metallicity, differ significantly from models that use the standard mass-loss rates, impacting our understanding of stellar populations at low metallicity and in the young Universe.
Gesehen am 09.09.2025